2019
DOI: 10.1111/joim.13009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolite biomarkers of boiled and filtered coffee intake and their association with type 2 diabetes risk

Abstract: Background Habitual coffee intake has been associated with a lower risk of developing type 2 diabetes (T2D), but few studies used biomarkers to reflect intake and investigated different coffee brews, that is boiled and filtered, separately. Objectives To identify plasma metabolites associated with boiled or filtered coffee intake and to examine their association with T2D risk in Swedish adults. Methods In a case–control study nested within the Västerbotten Intervention Programme, baseline plasma samples from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 61 publications
1
25
1
Order By: Relevance
“…[7][8][9][10] Plasma metabolites as the final products of biological processes reflect the interactions among these factors, while are broadly used as biomarkers for diagnosing the disease. [11][12][13][14] Metabolomics was widely applied in scientific researches since the 1990s, 15 which included untargeted and targeted strategies. 16 In our previous studies, we used the liquid chromatography/mass spectrometry (LC/MS), gas chromatography mass spectrometry (GC/MS), and nuclear magnetic resonance (NMR) spectroscopy-based untargeted metabolomics approaches to observe the metabolic changes in the plasma, peripheral blood mononuclear cells, and urine of depression patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Plasma metabolites as the final products of biological processes reflect the interactions among these factors, while are broadly used as biomarkers for diagnosing the disease. [11][12][13][14] Metabolomics was widely applied in scientific researches since the 1990s, 15 which included untargeted and targeted strategies. 16 In our previous studies, we used the liquid chromatography/mass spectrometry (LC/MS), gas chromatography mass spectrometry (GC/MS), and nuclear magnetic resonance (NMR) spectroscopy-based untargeted metabolomics approaches to observe the metabolic changes in the plasma, peripheral blood mononuclear cells, and urine of depression patients.…”
Section: Introductionmentioning
confidence: 99%
“…SCZ is caused by a variety of reasons, such as genetic, environmental, and psychological factors 7–10 . Plasma metabolites as the final products of biological processes reflect the interactions among these factors, while are broadly used as biomarkers for diagnosing the disease 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…[3] The majority of studies on coffee and tea consumption have been conducted on populations of European descent, who have higher consumption of coffee and/or different types of tea. [40,41] There is only one other Asian study (Hong Kong population) that identified 12 significant serum metabolites associated with coffee consumption, however these metabolites do not overlap with those measured or reported in our study, and tea consumption was not assessed. [42] This Singapore population study provides a unique opportunity to study the impact of coffee and tea consumption on metabolomics profiles.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, recent studies performed in Japan and Brazil, showed that decaffeinated coffee consumption improved insulin sensitivity in healthy men ( 102 , 103 ). Another study from Sweden showed an advantage of filtered over boiled coffee when it comes to the protective role of coffee on T2D development ( 104 ). It was suggested that long-term consumption of coffee beverages is associated with a lower risk of T2D, probably via multiple mechanisms, including effects on glucose homeostasis, oxidative stress and inflammation ( 105 ).…”
Section: Coffee In the Time Of Covid-19mentioning
confidence: 99%